2017
DOI: 10.1523/jneurosci.2161-17.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropeptide S Activates Paraventricular Oxytocin Neurons to Induce Anxiolysis

Abstract: Neuropeptides, such as neuropeptide S (NPS) and oxytocin (OXT), represent potential options for the treatment of anxiety disorders due to their potent anxiolytic profile. In this study, we aimed to reveal the mechanisms underlying the behavioral action of NPS, and present a chain of evidence that the effects of NPS within the hypothalamic paraventricular nucleus (PVN) are mediated via actions on local OXT neurons in male Wistar rats. First, retrograde studies identified NPS fibers originating in the brainstem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 71 publications
1
24
0
2
Order By: Relevance
“…In this regard, to target the oxytocinergic system, in particular with specific OTR agonist such as LIT-001, may be particularly relevant. Indeed, activation of OTR is known to induce a variety of molecular cascades 24 resulting in an important modulation of nociception 25 , social recognition and interactions 26,27 , anxiety 28 , feeding behavior 29 , and stress 30 , all important comorbidity factors in painful patients. www.nature.com/scientificreports www.nature.com/scientificreports/ Interestingly, a previous study has also shown that LIT-001 improved social interaction in a mouse model of autism 20 , reinforcing its putative interest as an analgesic molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, to target the oxytocinergic system, in particular with specific OTR agonist such as LIT-001, may be particularly relevant. Indeed, activation of OTR is known to induce a variety of molecular cascades 24 resulting in an important modulation of nociception 25 , social recognition and interactions 26,27 , anxiety 28 , feeding behavior 29 , and stress 30 , all important comorbidity factors in painful patients. www.nature.com/scientificreports www.nature.com/scientificreports/ Interestingly, a previous study has also shown that LIT-001 improved social interaction in a mouse model of autism 20 , reinforcing its putative interest as an analgesic molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Next, an AAV equipped with bidirectional tet promoter (P tet bi) expressing the Cre-recombinase was linked to a genetically-encoded calcium indicator (YC3.60) (Virus 2, rAAV-P tet bi-Cre/YC3.60, (L€ utcke et al, 2010)). As the last component of our viral technique (Virus 3), we generated rAAVs under the OT promoter to drive expression of hChR2-mCherry, GFP or hM4D(Gi)-mCherry (Eliava et al, 2016;Grund et al, 2017) in a Cre-dependent manner.…”
Section: The Vgate System Generation and Cloningmentioning
confidence: 99%
“…In addition to acting as an acute anxiolytic to diminish fear responses, mainly in the CeA and other areas (Litvin et al 2016;Viviani et al 2011;de la Mora et al 2016;Sabihi et al 2017;Grund et al 2017;Menon et al 2018), OTcould also act on fear learning, and fear extinction learning in a longlasting manner. In other words, it could work on neuronal plasticity in the fear-related neural networks.…”
Section: Oxytocin Treatment: Mode Of Actionmentioning
confidence: 99%